1987
DOI: 10.1042/bj2460393
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms for two amplification systems of insulin release

Abstract: The mechanisms whereby activation of the cyclic AMP-dependent protein kinase A or the Ca2+-phospholipid-dependent protein kinase C amplifies insulin release were studied with mouse islets. Forskolin and the phorbol ester 12-O-tetradecanoylphorbol 13-acetate (TPA) were used to stimulate adenylate cyclase and protein kinase C respectively. The sulphonylurea tolbutamide was used to initiate insulin release in the presence of 3 mM-glucose. Tolbutamide alone inhibited 86Rb+ efflux, depolarized ,-cell membrane, trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 42 publications
(72 reference statements)
2
27
1
Order By: Relevance
“…Carbachol activates PLC, increases IP accumulation but has little, if any, sustained effect on release in the presence of substimulatory glucose (Best & Malaisse 1983, 1984, Henquin et al 1988, Zawalich et al 1989b, Gilon & Henquin 2001. Forskolin activates adenylate cyclase (Seamon & Daly 1981) and potentiates insulin secretion in response to a large number of compounds (Wiedenkeller & Sharp 1983, Henquin et al 1987. Like carbachol, however, it is impotent at low glucose concentrations (Wiedenkeller & Sharp 1983).…”
Section: Impact Of Carbachol Forskolin or Wortmannin On Agonist-indumentioning
confidence: 99%
See 2 more Smart Citations
“…Carbachol activates PLC, increases IP accumulation but has little, if any, sustained effect on release in the presence of substimulatory glucose (Best & Malaisse 1983, 1984, Henquin et al 1988, Zawalich et al 1989b, Gilon & Henquin 2001. Forskolin activates adenylate cyclase (Seamon & Daly 1981) and potentiates insulin secretion in response to a large number of compounds (Wiedenkeller & Sharp 1983, Henquin et al 1987. Like carbachol, however, it is impotent at low glucose concentrations (Wiedenkeller & Sharp 1983).…”
Section: Impact Of Carbachol Forskolin or Wortmannin On Agonist-indumentioning
confidence: 99%
“…Information flow in both systems is activated by glucose and they appear integral for the maintenance of islet responsiveness (Henquin et al 1987). The studies with carbachol were based on our hypothesis that the activation of PLC provides those signals that play an important role in the regulation of several -cell response patterns, including a rising second phase of insulin release and the induction of TDP, in rat islets.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Insulin secretion from the pancreatic ␤-cell is tightly regulated by stimulatory signals generated during the intracellular metabolism of glucose and by neurohumoral agonists operative at the cell membrane (1)(2)(3)(4)(5). Most recently an additional layer of complexity has been added by reports suggesting that insulin exerts an autocrine stimulatory effect on insulin secretion from the ␤-cell (6,7).…”
mentioning
confidence: 99%
“…This concept was based primarily on amperometric measurements using ␤-cells preincubated in 5-hydroxytryptamine (5HT). 1 Because 5HT exposure exerts inhibitory effects on insulin release (8 -10), the precise physiologic significance of findings made with 5HT-preloaded ␤-cells is unclear. Moreover, previous studies exploring the potential role of insulin on stimulated secretion showed no effect (11) or supported the concept that insulin exerts a negative, not positive, feedback on its own secretion (12)(13)(14)(15).…”
mentioning
confidence: 99%